Studies on micropropagation, cellular behavior, photosynthetic and biological activities of red clover (Trifolium pratense L.) / Arash Khorasani Esmaeili - Arash Khorasani, Esmaeili (2016)
Tissue culture studies of a temperate forage crop, Trifolium pratense L. were investigated in the current project. In vitro regeneration of this species was successfully achieved in this study using nodal explants cultured on Murashige and Skoog (MS) media supplemented with different hormones at various concentrations and also on MS hormone free media as a control. Complete plant regeneration of T. pratense was best achieved when the nodal explants were cultured on MS media supplemented with 1.5 mg/l BAP and 0.5 mg/l IBA, with mean number of 6.05 ± 0.28 shoots per explant, and 100% of the explant samples produced shoots. On the other hand, the best root formation was obtained on MS media supplemented with 1.5 mg/l BAP and 0.75 mg/l IBA, with the mean number of 3.3 ± 0.21 roots per explant. However, the nodal explants cultured on MS hormone free medium failed to produce any shoots or roots. Callus formation was successfully achieved when the nodal explants were cultured on MS medium containing different types of plant hormones. MS medium supplemented with 1.5 mg/l BAP and 0.5 mg/l 2,4-D was the most responsive, whereby 100% of the explants managed to produce callus. Adaptation process to the natural environment or acclimatization, i,e. the transfer of in vitro grown plants to the ex vitro condition was successfully undertaken, with very high survival rates of plantlets (93.71 ± 4.64 %) when they were transferred to the combination of red soil and black soil with the ratio of 1:1. Subsequently, the extracts of in vivo and in vitro grown plants as well as callus tissues of T. pratense were tested for their antioxidant activities, using different extraction solvents and different antioxidant assays. The total flavonoid and phenolic contents as well as extraction yield of the extracts were also investigated to determine their correlation with the antioxidant activity of the extracts. Among all the tested extracts, the highest amount of total phenolic and total flavonoids content were found in methanol extract from in vivo grown plants. The antioxidant activity of tested samples followed the order; in vivo plant extract ˃ callus extract ˃ in vitro extract. The highest reducing power, 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical scavenging and chelating power were found in methanol extracts of in vivo grown T. pratense. Whilst the chloroform fraction of in vivo grown plants showed the highest 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, superoxide anion radical scavenging and hydrogen peroxide scavenging compared to the other tested extracts. A significant correlation was found between the antioxidant activity of extracts and their total phenolic and total flavonoid content. The cytotoxicity of the plant extracts were examined against two human cancer cell lines (human breast carcinoma (MCF-7) and human colon carcinoma (HCT-116)), using MTT assay. Four different extraction solvents were used to examine the effect of the solvent on cytotoxic activity of the extracts. Two cancer cell lines were treated with the extracts for 24, 48 and 72 hours. All of the examined extracts exhibited toxicity on the tested cell lines in a time dependent increase, but in a lower potency than doxorubicin (positive control). The chloroform fraction of in vivo grown plants showed the highest cytotoxic activity against the MCF-7 cell line (IC50 = 66.44 ± 2.05 μg/ml) but it was not significantly different with the cytotoxic activity of chloroform fraction of callus tissue (IC50 = 69.48 ± 2.66 μg/ml). The highest cytotoxic activity against the HCT-116 cell line was shown by the chloroform fraction of callus tissue (IC50 = 79.53 ± 2.00 μg/ml). The antimicrobial efficiency of extract derived from T. pratense (in vivo and in vitro grown plants, including callus) were examined using ethanol and methanol as solvents for extraction and tested against four bacterial pathogens (two gram negative and two gram positive) and three fungal pathogens. The antimicrobial activity of the methanol extract was found to give higher inhibition zone when compared with ethanol extract. Among the callus, in vitro and in vivo grown plants, the callus extract showed better antimicrobial activity, thus revealing a new potential use of T. pratense callus. To compare the photosynthetic parameters, the Stomatal conductance (gs), Transpiration rate (E) and Net photosynthetic (Pn) were determined for the plants grown under in vitro and in vivo conditions. A comparison was made for the observed data for the light-saturated photosynthetic among the treatments which revealed that the maximum photosynthetic rate (PNmax) was 18.3 and 11.3 μmol (CO2)/m2/s in in vivo and in vitro plant leaves, respectively. Respiration (Rd) and Compensation point (CP) were found 1.5-folds and two-folds higher in in vitro plants, respectively. On the other hand, the in vitro grown plants exhibited higher transpiration rate and also higher stomatal conductance compared with the in vivo plants. Consequently, high levels of differentiation in terms of photosynthesis parameters exist among the in vivo and in vitro samples. Significant direct relation was observed between net photosynthetic rate and total phenolic and flavonoid content of T. pratense leaves. The effect of optimal and supra-optimal concentrations of Sodium chloride (NaCl) on growth and antioxidant defence was also studied in the in vitro cultures of T. pretence. Seeds of T. pratense were germinated in Murashige and Skoog medium (MS) containing different concentrations of NaCl (0, 50, 100, 150, 200 mM). The lengths of roots and shoots as well as percentage of germination, free radical scavenging activity (DPPH) and Superoxide dismutase (SOD) were measured. A significant decrease in germination and growth was observed in the seeds exposed to 100, 150 and 200 mM salt. The highest percentage of germination was found in the MS medium containing 50 mM NaCl, although the highest root and shoot length were found in MS medium without NaCl. The highest antioxidant activity of methanol extract of the plants occurred in in vitro plants cultured in MS medium supplemented with 50 mM NaCl. A significant decrease in free radicals scavenging and superoxide dismutase activities were found in plants grown in media containing 100, 150 and 200 mM salt.